2018
DOI: 10.5812/aapm.64236
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oral Melatonin and Midazolam as Premedication in Children Undergoing General Anesthesia for Dental Treatment

Abstract: BackgroundDental anxiety is prevalent in children. This condition may cause uncooperative behavior and need a treatment under general anesthesia. The perioperative period, especially for children, is a stressing event. Premedication is commonly used to reduce perioperative anxiety and facilitate the induction of anesthesia.Methods132 children candidates for dental treatment under GA were enrolled in this study and randomly divided into 3 groups. Oral melatonin, midazolam, and normal saline were administered as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…As a premedicant, it has been used in children in a dose of 0.25–0.5 mg/kg 60 min prior to induction with varying results. [141516]…”
Section: Sedative Premedicationmentioning
confidence: 99%
“…As a premedicant, it has been used in children in a dose of 0.25–0.5 mg/kg 60 min prior to induction with varying results. [141516]…”
Section: Sedative Premedicationmentioning
confidence: 99%
“…The studies included in this review highlight the use of Of the 27 studies identified, only 7 (26%) were placebocontrolled, thus limiting the robustness of data on the effectiveness of melatonin. Another issue was the dosing variability of melatonin, with some studies using a dose per kg body weight and others using a fixed dose [50][51][52][53][54][55][56][57]. The oral bioavailability of melatonin is variable, ranging from 1 to 56%, with a mean of approximately 15% [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] compared the effect of oral melatonin and midazolam in alleviating preoperative anxiety and observed that preoperative melatonin administration is not effective in alleviating anxiety, as compared to midazolam. Faghihian et al [ 19 ]’s clinical trial randomly divided 132 children who were general anesthesia candidates for dental treatment into three groups receiving midazolam, melatonin, and normal saline as premedication, assessing and recording sedation scores before general anesthesia, easy venipuncture, the need for pain relief, and recovery time. Their result suggested that midazolam was preferable to melatonin as a premedication because of more sedation, easier venipuncture, less need for pain relief, and better recovery in children under general anesthesia for dental treatment, compared to melatonin, whereas our study showed better sedation score, ease of separation from parents, and admission of anesthesia with midazolam than melatonin.…”
Section: Discussionmentioning
confidence: 99%